Platelet Rich Plasma for Chronic Synovitis Treatment in Patients with Haemophilia. Issue 4 (4th May 2017) - Caviglia, H.; Landro, M. E.; Daffunchio, C.; Galatro, G.; Douglas Price, A. L.; Salgado, P.; Neme, D.
Abstract : Introduction: Haemophilic synovitis is caused by chronic accumulation of blood in the joint. Conservative treatment is insufficient to solve this pathology. Platelet‐rich plasma (PRP) has a high concentration of growth factors (GFs) that play a key role in regulation and stimulation of healing processes. The aim of this study was to describe the effect of PRP injection in chronic synovitis of the joints in patients with haemophilia (PWH). Patients and methods: Nineteen patients with 28 joints were treated at our centre in Buenos Aires, Argentina between December 2014 and December 2015. Eighteen were Haemophilia type A (17 severe, one mild) and one was type B severe. Mean age was 26 years old. Chronic synovitis was present in two ankles, seven elbows and 19 knee joints. All affected joints were evaluated for range of motion (ROM), perimeter, Haemophilia Joint Health Score (HJHS), number of bleedings episodes and Visual Analogue Scale (VAS). Evaluations were before treatment and 3 and 6 months after treatment. Results: A mean volume of 4 mL of PRP was injected into the joint cavity. The statistical analysis before and after treatments revealed a statistically significant ( P < 0.001) decrease in the HJHS score. Decrease in joint bleeding episodes was also statistically significant ( P < 0.001). All patients reported pain relief and VAS scores were statistically significant ( P < 0.001). Joint perimeter also showed a statistically significant difference ( P < 0.001). No complications were observed in any of the patients, either during blood collection or during PRP injection, even for inhibitor patients. Conclusion: Platelet‐rich plasma is a useful, safe, and inexpensive treatment for chronic haemophilic synovitis.